Nanostructured polymeric system based of cashew gum for oral admnistration of insulin - Silva,Eliadna de Lemos Vasconcelos (2019)
ABSTRACT The subcutaneous administration of insulin has been the treatment of millions of diabetics in the world. However, for such via insulin is invasive and not mimics the physiological action causing side effects. The oral route would be the most physiological and comfortable option, but the oral bioavailability of insulin is low by proteolytic activity and reduced permeability of the gastrointestinal tract. The aim of the study was to develop a nanostructured system integrating biomaterials for oral insulin delivery. Cashew gum (CG) is a polysaccharide extracted from the exudate of the plant Anacardium occidentale. It is a biopolymer composed of simple sugars and glucuronic acid and it can be used in nanostructured systems for the incorporation of molecules. The exudate was isolated, dissolved in water, filtered, precipitated in ethanol and purified. The CG was characterized by infrared spectroscopy and molecular weight by size exclusion chromatography. Nanoparticles were prepared through ionotropic gelation integrating cashew gum, dextran sulfate and poloxamer containing insulin stabilized with chitosan, poly(ethyleneglycol) and coated with albumin. The particles were analyzed for particle size, zeta potential and insulin entrapment efficiency. The FTIR spectrum for CG showed a band at 3395 cm-1 due to the stretching vibration of O-H, a band at 2926 cm-1 of C-H vibrations; absorption at 1639 cm-1 of O-H type from bound water molecules and bands at 1143, 1073 and 1024 cm-1 due vibrations of the C-O-C from glycosidic bonds and O-H of alcohols. The peak molar mass of GC was 2.35 × 104 g/mol. The particles had a size of 156 nm and after coating, size of 5387 nm with 92% insulin entrapment efficiency and zeta potential of -51 mV indicating electrostatic stabilization. The results suggest an innovative cashew gum base system for oral insulin administration.